Soybean protease inhibitors increase Bacillus thuringiensis subs. israelensis toxicity against Hypothenemus hampei = Inhibidores de proteasas de soya incrementan la toxicidad de Bacillus thuringiensis subs. israelensis contra Hypothenemus hampei - Mesén Porras, Esteve Alonso 1990-; Dahdouh Cabia, Segio; Jimenez Quiros, Catherine; Mora Castro, Rebeca; Rodríguez Sánchez, César Augusto 1979- (2020)
Introduction. The coffee berry borer (Hypothenemus hampei Ferrari, CBB) is one of the most devastating pests on coffee plantations around the world. Although CBB is susceptible to the effect of δ-endotoxins of Bacillus thuringiensis subs. israelensis (Bti) at laboratory level, the efficacy of this control method is poor in the field, presumably due to the inactivation by digestive proteases different to those required for protoxin activation. Objective. To study whether the addition of a soybean flour extract enriched with protease inhibitors (PI), mixed with Bti crystals and spores (Bti-sc) in an artificial diet, could improve the toxicity of Bti against CBB. Materials and methods. This study was performed in San José, Costa Rica, between 2012 and 2013. A set of adult female CBB insects was exposed to a mixture containing different concentrations of a partially purified soybean meal extract with active PI and lyophilized Bti-sc, and were tested through a bioassay in artificial diet to estimate the sub-lethal concentration (LC50). The mortality results were validated by observing the dissected midgut, whose ultrastructure was analyzed by transmission electron microscopy. Results. The soybean extracts partially degraded the Bti-sc complex, it reduced its LC50 by almost four times (from 1.135 to 0.315 μg μl-1) and enhanced CBB mortality in a concentration-dependent manner. Histological analyses of the midgut confirmed this synergistic effect, since severe epithelial damage to the intestinal epithelium of CBB exposed to Bti-sc + PI was visualized compared to Bti-sc alone. Conclusions. The combination of a soybean extract enriched in PI and Bti-sc enhanced the mortality effect over CBB, which was confirmed by the midgut collapse. Soybean flour is a cost-effective supplement that could increase Bti effectiveness against CBB and delay the appearance of biological resistance.
Introducción. La broca del café (Hypothenemus hampei, CBB) es una de las plagas más devastadoras en plantaciones de café alrededor del mundo. Aunque CBB es susceptible al efecto de las δ-endotoxinas del Bacillus thuringiensis subs. israelensis (Bti) a nivel de laboratorio, la eficacia de este método de control es deficiente en campo, posiblemente debido a la inactivación ocasionada por proteasas digestivas diferentes a las requeridas para la activación de las protoxinas. Objetivo. Determinar si la incorporación de un extracto de harina de soya con inhibidores de proteasas (PI) mezclado con cristales y esporas de Bti (Bti-sc) en una dieta artifical, podría mejorar la toxicidad de Bti contra CBB. Materiales y métodos. Este estudio se realizó en San José, Costa Rica entre 2012 y 2013. Se expuso un conjunto de insectos hembras adultas de CBB a una mezcla que incluyó diferentes concentraciones del extracto de soya parcialmente purificado con PI activo y un liofilizado de Bti-sc, y fueron evaluadas mediante un bioensayo en dieta artificial para estimar la concentración subletal (CL50). Los resultados de mortalidad se validaron mediante observación del intestino medio diseccionado, cuya ultraestructura se analizó mediante microscopía electrónica de transmisión. Resultados. El extracto de soya degradó parcialmente el complejo Bti-sc, redujo la CL50 en casi cuatro veces (de 1,135 a 0,315 μg μl-1) y potenció la mortalidad de CBB de manera concentración-dependiente. Los análisis histológicos del intestino medio confirmaron este efecto sinérgico, dado que se visualizaron daños severos en el epitelio intestinal de CBB expuestos a Bti-sc + PI comparado con Bti-sc solo. Conclusiones. La combinación del extracto de soya enriquecido con PI y Bti-sc potenció la letalidad sobre CBB, que se confirmó por el colapso intestinal. La harina de soya es un suplemento económico que podría aumentar la efectividad de Biti para controlar CBB y ...
En Revista Agronomía mesoamericana
Volumen 31, número 2 (mayo-agosto 2020)
Descripción basada en el contenido visto el 21 de agosto, 2023
También disponible en formatos EPUB, HTML y XML
Keywords: BROCA DEL CAFETO; CONTROL BIOLOGICO DE PLAGAS; TOXINAS BACTERIANAS; ENZIMAS PROTEOLÍTICAS; HARINA DE SOYA; INHIBIDORES DE PROTEASA